PERANAN PENGELOLA PROGRAM KESETARAAN PADA ANAK BERKEBUTUHAN KHUSUS DI PKBM KAK SETO PEKANBARU - Ina Anggela; Said Suhil Achmad; Sumardi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The formulation of the problem in this research is how the role of equality program manager in children with special needs in PKBM Kak Seto Pekanbaru? The purpose of this study is to find out how the role of equity program managers in children with special needs in PKBM Kak Seto Pekanbaru. Data collection techniques of this study using observation, interview, documentation and triangulation. The results of the research conducted can be concluded that the way the manager runs his role in equality programs in children with special needs in PKBM Kak Seto Pekanbaru is by way of information outside the institution by following training and seminars on children with special needs, then the manager collects information obtained from Each activity followed by each of its staff. Information received both inside and outside the organizing organization collects, and disseminates information received by the manager to all staff at the meeting. In the meeting, the manager takes a decision about the problem or solution related to the development of equality programs for children with special needs, the process of decision-making determined by the manager of course the results of negotiations made with his subordinates and the agreement of the homescholling center.Keywords: Role of manager, equality program, children with special needs